Drought, Sulphate Acidifications & Saline Intrusion in Mekong Delta, Caused by the Hydro-Electric Dams in Upstream of River, and Climate Change - Ba Le Huy; Hoan Nguyen Xuan; Hung Le; Nam Thai Van; Phong Nguyen Tan; Thanh Le Minh (Drought, Sulphate Acidifications & Saline Intrusion in Mekong Delta, Caused by the Hydro-Electric Dams in Upstream of River, and Climate Change, 2022)
The causes of drought, alum, and saltwater intrusion in the Mekong Delta, Vietnam are The hydro-electric dams (China, Laos, Thailand), mainly in China. The total amount of water that they block accounts for over 65% of the Mekong River basin water resources. The mainstream of the Mekong flows downstream, causing the river to dry up, traffic difficulties, lack of water to irrigate rice fields, and lack of water for people’s livelihood, especially in the dry season. But lack of water has caused great harm: Sulfate acidification and salinization become very high. Because this is the Wetland, young. On the soil horizon, there are 3 Layers: 0-20cm: New alluvium; layer 20-50 cm: Jarosite layer: sediments of Fe, Al double sulfate; Floor 50-150 cm: Pyrite with a very high concentration of S (>5%). Drought will make the acidification process more intense. At the same time, drought creates conditions for tidal infiltration to a depth of 70-100km, causing salinization; plants cannot tolerate salt concentrations <4g/L. The damage to the Mekong Delta is enormous.